THE IMPACT OF INFORMATION TECHNOLOGY ON HUMAN RESOURCE DEVELOPMENT - Rawan Abdulrazzaq Ekal; Alassaad Lakhal (Scholars Digest Publishing, 2023)
Purpose: This study explores the relationship between Information Technology and human resource development in the context of Iraqi universities in Diyala province. The objectives were to examine the impact of Information Technology dimensions (Physical components, Software, Communication Networks, Ability) on human resource development and provide recommendations for enhancing human resource development based on the findings. The study employed descriptive statistics and regression analysis to analyze the data collected from a sample of Iraqi universities in Diyala province. The results revealed There is a statistically significant impact of using Information Technology on Human Resource Development within Iraqi universities in Diyala province. Based on these findings, the study recommends that Iraqi universities in Diyala province Enhancing ICT Utilization, Human Resource Development Enhancement, Leveraging ICT for HRD. Design/methodology/approach: The study used a descriptive-analytical approach to investigate the relationship between Information Technology (ICT) as an independent variable and Human Resource Development (HRD) as a dependent variable. Secondary data from various sources, including books, academic studies, and research articles, were used to establish the study's theoretical framework. Primary data for hypothesis testing were gathered through a field survey questionnaire administered to employees in Diyala Province's Iraqi universities, utilizing a comprehensive sampling method. Statistical methods were then applied to the initial data to summarize and describe the correlations and impacts between the study variables.
Keywords: Information Technology, Human resource development, Iraqi universities in Diyala province.